TINGKAT PARTISIPASI PEREMPUAN DALAM PENYELENGGARAAN PEMERINTAHAN DESA BULUCENRANA KECAMATAN PITU RIAWA KABUPATEN SIDENRENG RAPPANG - Basmiati Jufri Jufri (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract This study aims to determine the level of women's participation in the administration of village governance and the factors that influence the level of women's participation in the administration of the village of Bulucenrana. The population of this study was 1,231 families and a sample of 92 households. The sampling technique used is Purpossive Sampling. This type of research is quantitative descriptive. Data collection techniques are observation, interviews, library research and questionnaires. Data analysis techniques use statistics with helped SPSS v.16. The results showed that the participation of women 56% was not good consisting of money participation 59%, participation of property 59%, participation of personnel 56%, participation of skills 49%, participation of ideas 58%, and also social participation 57%. The implementation of Village Government 54% is not good consisting of services 61%, empowerment 50%, and development 52%. Based on SPSS v.16 using the regression formula, the economic aspects of 22%, socio-cultural aspects 41%, geographic aspects of the region 81% affect the level of women's participation in the administration of the Village Government of Bulucenrana. Keywords: Women's Participation and Implementation of Village Government